The 2019 Australian election. Issue 1 (March 2020) - Johnson, Carol
Opinion polls suggested that Australia's Coalition (Liberal and National Party) government was likely to be replaced by a Labor government at the 2019 election. However, in fact the government was returned. Key issues in the 2019 election centred around managing the economy, including levels of taxation and issues of inequality; around spending on government services such as health and education; and around issues of climate change. There were elements of populism in both major parties' campaigns, and two minor populist parties played a significant role in preference distribution. There were also some simmering issues that reflect the broader geopolitical and geo-economic changes that are impacting upon Australia. These include not only challenges for Australia's economy and identity in the 'Asian Century', but also issues of Australia's relationship with China.